EFEKTIFITAS TEKNOLOGI DIGITAL : STRATEGI PENGEMBANGAN USAHA CV. ALWI JAYA - Oktafio Rizky Fernanda; Hadi Ismanto (CV. Denasya Smart Publisher, 2025)
This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation of the company’s digital marketing activities. The results show that the application of digital technology has had a significant impact on expanding market reach, increasing the effectiveness of promotions, and enabling the company to obtain real-time, accurate, and measurable marketing data. One example is the A/B testing of Facebook Ads, where a campaign targeting the Balikpapan area achieved a higher audience reach compared to a campaign targeting Samarinda. The conclusion of this study states that the use of digital technology in marketing at CV. Alwi Jaya is effective in increasing brand visibility and reducing promotional costs. The data-driven strategy implemented helps the company make more objective marketing decisions and adapt to the digitalization developments in the modern era.